Effect of the Papaya Latex on the Visibility of Fingerprint - Chantira Boonsri; Pichet Limsuwan; Prathan Buranasiri (My University, 2020)
The effect of the papaya latex on the visibility of fingerprint was investigated. The fingerprints of the thumb without and with touching papaya latex for 5 and 10 min were prepared on the glass slides and captured by CMOS camera. The fingerprint images were reconstructed and the transverse intensity profiles were performed. The valley depth and the ridge width for these prepared fingerprints were determined. The results show that the visibility of the fingerprints increased with increasing touching time with papaya latex. It can be concluded that the finger surface needed to be scanned using any fingerprint sensors should be touched with papaya latex for about 10 min before image scanning to increase the image quality.
Keywords: Visibility; Wood and Agarwood Research